2011
DOI: 10.1089/thy.2009.0358
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Age and Point of CareTSH Testing in the Monitoring of Iodine Deficiency Disorders: Findings from Western Uganda

Abstract: Assessing neonatal TSH levels in developing countries with a TSH assay method suitable for field use can be successfully used to screen for congenital hypothyroidism and to indirectly assess a population's iodine status. Based on the percentage of neonates with TSH values >5 mIU/L, presumptive iodine deficiency persists in western Uganda. This finding suggests that continued monitoring of iodine nutrition in the area surrounding the Rwenzori Mountains in Uganda and Congo is needed. Due to the progressive fall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…We included eight children in this study. Despite the small sample size, which would be a limitation to this descriptive study, our results reflect how under-diagnosed the condition is (10)(11)(12)(13). Indeed, in the absence of newborn screening, Tal Our patients were younger than those diagnosed in the study done in Senegal (17), but we also noticed, like the authors (17), a delay in the management of patients.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…We included eight children in this study. Despite the small sample size, which would be a limitation to this descriptive study, our results reflect how under-diagnosed the condition is (10)(11)(12)(13). Indeed, in the absence of newborn screening, Tal Our patients were younger than those diagnosed in the study done in Senegal (17), but we also noticed, like the authors (17), a delay in the management of patients.…”
Section: Discussionsupporting
confidence: 41%
“…Studies on neonatal screening performed in Nigeria, Uganda and Ethiopia showed few or no cases of congenital hypothyroidism (11)(12)(13)(14). But some methodological difficulties can explain this unexpected results.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to apply the frequency of neonatal TSH values of more than 5 mIU/L in determining population iodine status and monitoring intervention programs. [ 26 27 28 ] Studies conducted amongst neonates have documented that ID during the initial phase of life affects the developing brain. Thyroid stimulating hormone affects proper development of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to apply the frequency of neonatal TSH values of more than 5 mIU/L in determining the population iodine status and monitoring intervention programs. [ 18 19 20 ] Studies conducted among neonates have documented that ID during the initial phase of life affects the developing brain. TSH affects proper development of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%